2020
DOI: 10.1590/s1678-3921.pab2020.v55.01756
|View full text |Cite
|
Sign up to set email alerts
|

Snake venoms and purified toxins as biotechnological tools to control Ralstonia solanacearum

Abstract: The objective of this work was to evaluate the in vitro antibacterial activity of snake venoms and purified toxins on the phytopathogenic bacterium Ralstonia solanacearum. The evaluations were performed with 17 crude venoms (13 from Bothrops, 3 from Crotalus, and 1 from Lachesis) and seven toxins (1 from Bothrops and 6 from Crotalus). Antibacterial activity was assessed in MB1 medium containing solubilized treatments (1 μL mL-1). A total of 100 μL bacterial suspension (8.4 x 109 CFU mL-1) was used. After incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Furthermore, it was reported that p-bromophenacyl bromide (p-BPP) presents a significant decrease in enzymatic activity and associated antibacterial activities, thereby destabilizing the membrane bilayer. Regarding PLA 2 crotoxin A or B (PLA 2 -CA and PLA 2 -CB), Alves et al [11] reported that both from C. durissus terrificus showed high bactericidal activity against R. solanacearum. Similarly, Samy et al [19] reported that crotoxin B of C. durissus terrificus and daboiatoxin of Daboia russelli presented the most robust bactericidal activity against the two strains of B. pseudomallei (TES and KHW).…”
Section: Bactericidal Effects Of Snake Venom Pla 2 Smentioning
confidence: 99%
“…Furthermore, it was reported that p-bromophenacyl bromide (p-BPP) presents a significant decrease in enzymatic activity and associated antibacterial activities, thereby destabilizing the membrane bilayer. Regarding PLA 2 crotoxin A or B (PLA 2 -CA and PLA 2 -CB), Alves et al [11] reported that both from C. durissus terrificus showed high bactericidal activity against R. solanacearum. Similarly, Samy et al [19] reported that crotoxin B of C. durissus terrificus and daboiatoxin of Daboia russelli presented the most robust bactericidal activity against the two strains of B. pseudomallei (TES and KHW).…”
Section: Bactericidal Effects Of Snake Venom Pla 2 Smentioning
confidence: 99%